Stingless Bee Beekeeping as a Coping Strategy of Poor Households to Cope with Impacts of Disasters in Lombok Island, Indonesia - Baiq Yulfia Elsadewi Yanuartati; Rinda Desan; Syarifuddin Syarifuddin; Ni Made Wirastika Sari; Muhammad Nursan (Jurnal Biologi Tropis, 2022)
Communities in Lombok, especially North Lombok, have faced several disasters in recent years. The disasters include the Earthquake in 2018 and the Covid-19 pandemic that began in 2020, having a social and economic adverse impact. During these disasters, Trigona (stingless bee) was observed of being an income activity that was quickly recovered. This study looks at how Trigona helped beekeepers as a coping strategy after facing disasters. A qualitative study was conducted in North Lombok by conducting interviews using open questions with interview guidance. The interviews involved 35 beekeepers as participants and two key informants who were related to the activities of beekeepers in the society. The data was analyzed qualitatively and the findings were presented descriptively. This study found that Trigona was a household business that was able to help farmers coped with the impacts of disasters in North Lombok. The beekeeping could recover soon after the 2018 earthquakes, and was survived during pandemi because it was supported by five livelihood assets, which were available around them, easy to access, easy to use, and/or profitable. The assets included natural, human, social, physical, and financial assets for both beekeeping and livelihoods. Trigona beekeeping was also supported by institutions, both formal and informal.